Determinants of Sharia-compliant and Non-compliant Capital Structure in the Cyclical Consumer Sector - Putri, Indira Pramestya; Khairunisa, Shalsabila; Silfhia, Mega; Pramudiani, Jeni Putri; Leon, Farah Margaretha (Universitas Proklamasi 45, 2024)
Indonesia is a predominantly Muslim country, so investing in stock instruments that comply with Sharia provisions is a major concern for investors in Indonesia. This research aims to compare the determining factors of capital structure in Sharia and non-sharia companies. This research sample used a purposive sampling method to obtain 66 shariah-compliant and 30 noncompliant companies from the cyclical consumer sector listed on the Indonesia Stock Exchange form 2020-2022 and used panel data regression. Profitability and liquidity have a negative effect on shariah-compliant and noncompliant leverage. Size has a positive effect on shariah-compliant and noncompliant leverage. EVAL has a negative effect on shariah-compliant market leverage and a significant positive effect on noncompliant book leverage. In noncompliant, GDPG has a positive effect on market leverage. The novelty of this study is to add business risk as an independent variable. This study is expected to guide financial managers on the use optimal capital structure in sharia and non-sharia companies to increase the shareholders wealth. Investors are recommended to choose enterprises with high level of profitability, liquidity and size, as well as low earnings volatility.